Relationship Between Servant Leadership, Leader-Member-Exchange, Organization Learning and Innovative Work Behavior: Evidence From High-Tech Firms - Shoukat Iqbal Khattak; Muhammad Anwar Khan; Muhammad Iftikhar Ali; Hafiz Ghufran Ali Khan; Imran Saeed (SAGE Open, 2023)
With the growing development of the knowledge economy in recent years, the value of knowledge workers has increased substantially. On the basis of the broaden-and-build theory (B&B theory) and conservation of resources (CoR) theory the aim of this research work is to evaluate the mediating effect of leader-member exchange (LMX) and organizational learning (OL) between servant leadership and knowledge innovative work behavior (IWB). Current study included the participation of 496 knowledge employees from China’s high-tech companies. The responses of the survey were analyzed using MPLS software while utilizing the structural equation modeling method. The findings validated the link between servant leadership (SL) and IWB. In the relationship between SL and IWB, LMX and OL mediated the relationship as parallel mediator. This study discovered a correlation between SL and OL and LMX. In addition, the findings signify that in the Chinese high-tech companies’ SL style augments IWB through the support of OL and LMX. The results of the study are useful for harnessing the leader and member for achieving organizational objectives through enhancing the innovative work behavior in the knowledge workers of Chinese high-tech companies.